A Nanostructured PLGA System for Cell Delivery of a Tetrathiahelicene as a Model for Helical DNA Intercalators1. Issue 3 (4th December 2014) - Cauteruccio, Silvia; Bartoli, Cristina; Carrara, Claudio; Dova, Davide; Errico, Cesare; Ciampi, Giulia; Dinucci, Dinuccio; Licandro, Emanuela; Chiellini, Federica
Abstract A novel nanoconstruct based on poly(lactic‐co‐glycolic acid) nanoparticles loaded with a tetrathiahelicene molecule conjugated to a fluorescent rhodamine probe was prepared and characterized. Because helicenes are known to be very promising DNA intercalators, the tetrathiahelicene was selected for this study as a model therapeutic cytotoxic molecule. The ability of the nanoconstruct to internalize the tetrathiahelicene and deliver it intracellularly in a safe manner has been investigated by means of cytotoxicity and cell uptake tests on Balb/3T3 clone A31 fibroblasts. The outcomes of this study suggest the suitability of the developed nanoconstruct to act as a vector for the intracellular delivery of hydrophobic small molecules, such as helicenes, thus contributing to their possible future exploitation as novel therapeutics.